Knowledge of Personal Hygiene among Food Handlers in Canteen at Faculty of Medicine, Universitas Padjadjaran, October to November 2012 - Drasthya Zarisha; Budi Darmawan; Ardini S. Raksanagara; Elsa Pudji Setiawati (Althea Medical Journal, 2015)
Background: Food borne diseases are caused by contamination of pathogenic microorganism and are still a major health problem throughout the world. There are 1,8 billion cases of diarrhea which mostly were caused by food contamination in 2005. Food handlers are at risk of contaminating microorganism towards food they handle. The process of transmission can be prevented by practicing good hygiene while processing and handling food. The objective of this study was assessing knowledge among food handlers regardingtheir personal and food hygiene at canteen in Faculty of Medicine, Universitas Padjadjaran.Methods: A descriptive study was conducted during the period of October to November 2012 to 14 food handlers in the Canteen at Faculty of Medicine, Universitas Padjadjaran using 26 validated questions divided into 3 major parts, 14 questions for knowledge of hand washing, 9 questions for knowledge of utilization of clean water and 3 questions for knowledge of waste management. The scores were classified as good, moderate, and poor. Data were analyzed using frquency distribution.Results: Majority of the respondents was male and common age group was 20–29 years old. Eight of the respondents were senior high school graduates. Based on working experience, majority of food handlers had been working for one and three years. None of the respondents had good knowledge. Only 12 and 2respondents had moderate and poor knowledge, respectively.Conclusion: None of the respondents had good knowledge regarding hand washing, utilization of clean water and waste management. Therefore, there is a need in providing more education about those aspects.[AMJ.2015;2(1):245–9]